Rhipicephalus sanguineus sensu lato (Acari: Ixodidae) nymphs: An ultrastructural study of the integument and midgut - Oliveira, Patricia Rosa de [UNESP]; Calligaris, Izabela Braggiao [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (Elsevier B.V., 2014)
This is an ultrastructural study of two important organs of ticks: the integument, covering the body and involved in the molting process, and the midgut, the first organ to have contact with the ingested host blood. The integument of Rhipicephalus sanguineus sensu lato freshly engorged nymphs consists of a layer of epidermal cells rich in organelles and a cuticle, subdivided in epicuticle and procuticle. The latter presents two distinct regions: the exocuticle (with several pore canals) and the endocuticle (secreted in highly organized overlaid lamellae). The midgut of R. sanguineus sensu lato freshly engorged nymphs consists of an epithelial wall formed by two types of cells: the generative cells, with few organelles; and the digestive cells, with several endosomes, digestive vacuoles, hematin residual bodies, and small drops of lipid. (C) 2014 Elsevier GmbH. All rights reserved.
Keywords: Rhipicephalus sanguineus; Tick; Nymphs; Morphology; Ultrastructure